Psychological Concerns of Children Undergoing Kidney Transplantation During the Pandemic: Single-centre Experience. Issue 1 (29th July 2021) - Paessler, Alicia; Boyle, Sheila; Marks, Stephen; Kessaris, Nicos; Stojanovic, Jelena
Abstract : Many paediatric kidney transplant programmes were closed during the COVID-19 pandemic, and due to the vulnerable nature of patients with end-stage kidney disease (ESKD), there were new concerns once these programmes reopened. We surveyed children and families who received a kidney transplant during the pandemic. We found that half of the participants felt scared and/or anxious about receiving a kidney transplant during the pandemic, and 2/8 participants were worried about catching COVID-19 during their recovery. While detailed counselling and additional safety precautions contributed to a good experience, patients and parents still demonstrated fear towards transplantation.